Physiological response and earliness of soybean genotypes to soil base saturation conditions - Alves de Andrade, Cristiane (2020)
Low base saturation (V) is one of the major abiotic stresses in the Brazilian Cerrado. Given this scenario, it is important to evaluate different physiological responses of genotypes in environments with and without liming aiming at select both liming responsive and low-saturation tolerant genotypes. The hypothesis of this study is that contrasting V conditions provide changes in physiological performance of soybean genotypes. Thus, our objective was to select soybean genotypes in environments with recommended and low V. Two field experiments were carried in randomized block design with three replicates and 10 F3 soybean genotypes (P1, P2, P3, P4, P5, P6, P7, P8, P9 and P10). In the first experiment, genotypes were evaluated without V correction (V = 30%), while in the second experiment, a liming was performed three months before to raise V to 60%. The traits evaluated were as follows: calcium and magnesium contents, days for maturation, transpiration, net photosynthesis, stomatal conductance and internal CO2 concentration. Our findings indicate that the physiological performance of soybean genotypes depends on the saturation condition. The P9 genotype obtained the best physiological performance under recommended V and can be used to obtain F3:4 lines physiologically responsive to soil correction. The P5 genotype obtained the best physiological performance at low V and can be used to obtain F3:4 lines aiming at a higher tolerance to low saturation. Considering that the Brazilian soils, especially in the Cerrado, are mostly poorly fertile, our study provide crucial information for soybean breeding programmes aiming at selecting genotypes tolerant to limiting environmental conditions.